Trabalhadores negros construindo sistema no solo. (Museu Afro-Digital, 2025)
Collection: Trabalho negro na Bahia
Keywords: Working class–Brazil–History; Black people–Brazil–History; Black people–Brazil–Social conditions; Black Workers; Labour History